2023
DOI: 10.1155/2023/1265449
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β and Allergy: Focusing on Its Role in Allergic Rhinitis

Abstract: Allergic rhinitis (AR) is a chronic upper airway immune-inflammation response mediated by immunoglobulin E (IgE) to allergens and can seriously affect the quality of life and work efficiency. Previous studies have shown that interleukin-1β (IL-1β) acts as a key cytokine to participate in and promote the occurrence and development of allergic diseases. It has been proposed that IL-1β may be a potential biomarker of AR. However, its definitive role and potential mechanism in AR have not been fully elucidated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…The top 20 targets ranked according to degree value were considered to have significant effects, including IL-1β, IL-6, TNF, IFNG, and IL-4. IL-1β has pro-inflammatory effects and is an important cytokine involved in and contributing to the development of AR, playing an important role in regulating the immune system in vitro and in vivo [ 41 ]. Meanwhile, IL-1β, a signature inflammatory factor secreted upon activation of NLRP3 inflammatory vesicles, plays a key role in the pathogenesis of AR [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The top 20 targets ranked according to degree value were considered to have significant effects, including IL-1β, IL-6, TNF, IFNG, and IL-4. IL-1β has pro-inflammatory effects and is an important cytokine involved in and contributing to the development of AR, playing an important role in regulating the immune system in vitro and in vivo [ 41 ]. Meanwhile, IL-1β, a signature inflammatory factor secreted upon activation of NLRP3 inflammatory vesicles, plays a key role in the pathogenesis of AR [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown increased IL-1β in the nasal mucus of patients with AR and that it acts as a key factor in the promotion of occurrence and development of AR [71][72][73] via the ROS-NLRP3-Caspase1-IL-1β signaling pathway [74,75]. It has even been proposed that IL-1β may be a potential biomarker of AR [76]. IL-1β is immediately released from cells within 1 to 2 h after allergen exposure [77] and gradually returns to the basal concentrations after 24 h [78].…”
Section: Discussionmentioning
confidence: 99%
“…This was also demonstrated by the results of our ELISA experiments, which were consistent with our ow cytometry results. IL-1β is a key cytokine that promotes the occurrence of AR 12 . IL-1β activates NF-κB pathway to promote IL-13 production 13 .…”
Section: Discussionmentioning
confidence: 99%